POTENSI DAYA HAMBAT EKSKTRAK KULIT BUAH MANGGIS (Garciniamangostana L) TERHADAP PERTUMBUHAN CANDIDAALBICANS - Ridha Andayani; Abdillah Imron Nasution; Andrian Andrian (Journal of Syiah Kuala Dentistry Society, 2016)
Candidaalbicans (C. albcians) is anopportunistic fungi that incertain circumstances may be pathogenis in the oral cavity and causes oral candidiasis. Garciniamangostana L. peels is one of plants which contains antifungal constituents such as flavonoid, tanins, saponins, polyphenols, quinones, and triterpenoids. This study was aimed to determine the effect of Garcinia mangostana L. peels extract against the growth of C.albicans.Garcinia mangostana L. peels extract was made by maceration method using 96% etanol. The determination of the effect of Garciniamangostana L. peels extract against the growth of C. albicans wa s done by using discdiffusion method on SDA media. Concentration of extract that has used is 6,25%, 12,5%, 25%, and 50%. The data collected from this study was analyzed by One Way ANOVA test with =0,05 and continued by LSD test. Result of this study showed. Conclution Garcinia mangostana peels extract have intermediet effect to against the growth of C. albicans on concentration 50% with inhibition zona 14,17 mm.Keyword: Candidaalbicans,Garciniamangostana L .peels extract,disc diffusion method